2021
DOI: 10.1021/acsphotonics.1c00299
|View full text |Cite
|
Sign up to set email alerts
|

Mark Stockman: Evangelist for Plasmonics

Abstract: Mark Stockman was a founding member and evangelist for the plasmonics field for most of his creative life. He never sought recognition, but fame came to him in a different way. He will be dearly remembered by colleagues and friends as one of the most influential and creative contributors to the science of light from our generation.■ A SHORT BIOGRAPHY OF PROFESSOR MARK STOCKMAN Mark Stockman was born on the 21st of July 1947 in Kharkov, a major cultural, scientific, educational, and industrial center in the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 154 publications
0
1
0
Order By: Relevance
“…I . Stockman [15,16], and throughout the time has paved its way up as a miniature source of spectrally tunable stimulated emission [17,18]. Apart from the mainstream research, spaser has found numerous applications in different areas such as opto-electronic systems [19][20][21][22][23][24][25], sensing in biological and chemical agents [26][27][28] and also as a biological probe [29,30] in disease therapeutics and diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…I . Stockman [15,16], and throughout the time has paved its way up as a miniature source of spectrally tunable stimulated emission [17,18]. Apart from the mainstream research, spaser has found numerous applications in different areas such as opto-electronic systems [19][20][21][22][23][24][25], sensing in biological and chemical agents [26][27][28] and also as a biological probe [29,30] in disease therapeutics and diagnostics.…”
Section: Introductionmentioning
confidence: 99%